زراعة القوقعة .. تحد أخر في الجزائر - صالحي, طارق (جامعة الوادي University of Eloued, 2018)
يعرض الباحث في هذه الورقة العلمية تقنية زراعة القوقعة , وما لها من فائدة ترجع بالإيجاب على مستوى الأطفال الذين فشلت معهم الآلات السمعية التقليدية في إيصال الأصوات وحرمانهم من دخول عالم الصوت, وتعلم النطق والكلام. The researcher presents in this scientific paper the technique of cochlear implantation, and its positive benefit for children who failed with traditional audio machines in the delivery of sounds and depriving them from entering the world of sound, and learn pronunciation and speech by addressing the conditions of children candidates for this technique and who must meet the requirements. Cochlear implantation is a new scientific compensation, enables the child to compensate for hearing loss at an early age and allows him to acquire basic language abilities, represented in the auditory understanding and linguistic expression, which is gained naturally in all language component levels. In addition to another sophisticated capacity which is "the higher language " , i.e the ability to organize language and its use as an thinking tool, and if not reached it becomes difficult to acquire reading and writing through this technique
مقال
Keywords: زراعه القوقعة - الاعاقة السمعية - النطق; cochlear implantation; hearing disability; pronunciation